Economic Aspects of the Rapeseed and Wheat Market Development in Poland in 1997–2007 - Kucharski, Krzysztof (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2008)
In this article an analysis and an evaluation were conducted of the processes which occurred on Polish rape-seed and wheat market at the end of the 20th century and the start of the 21st century. The time span in question covers the years from 1997 to 2007. This was a specific decade as it covered both the pre-accession period and the first years of Poland’s membership of the European Union. The agricultural sector is closely linked to other sectors of the economy, therefore the performance of the entire economy may not be neglected. Consequently, in the first part of the article the key macroeconomic indicators were defined as well as the indicators relating to the agricultural sector, i.e. the ‘agricultural price scissors’ index and the dynamics of the overall agricultural production. In the second part of the article the situation observable in the rapeseed and wheat market was described, including endogenous determinants thereof. Despite the growing influence of macroeconomic factors, endogenous determinants continued to be decisive for the rapeseed and wheat market in Poland. Development trends on the rapeseed and wheat market were to a greater extent contingent upon the cropping structure and yield than on business-cycle factors.
Keywords: macroeconomic factors; wheat market; rapeseed market